2021
DOI: 10.1007/s10389-021-01590-2
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreak investigation process in low- and middle-income countries: a systematic review of the methods and costs of contact tracing

Abstract: Aim The occurrence of measles outbreaks has increased, and previously measles-free countries are experiencing a resurgence, making measles elimination by 2020 unlikely. Therefore, outbreak prevention and rapid response strategies will need to be intensified. This systematic review therefore examines whether contact tracing (CT) as compared to no CT is an effective means of reducing measles spread during outbreaks in low-and middle-income countries (LMICs). Subject and methods A systematic review was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The health consequences of measles and rubella infections can be lifelong and include economic losses for individuals, families and societies. [ 31 ] This study analyzed publicly available annual summary data of reported imported and domestic measles and rubella cases from 2011 to 2020 published by the TCDC and is the first report covering such an area in Taiwan in the past 10 years. During the period of investigation, more than 90% of the cases of measles and rubella were imported from Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…The health consequences of measles and rubella infections can be lifelong and include economic losses for individuals, families and societies. [ 31 ] This study analyzed publicly available annual summary data of reported imported and domestic measles and rubella cases from 2011 to 2020 published by the TCDC and is the first report covering such an area in Taiwan in the past 10 years. During the period of investigation, more than 90% of the cases of measles and rubella were imported from Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Contact tracing has been adopted as a public health practice since the 19th century. It has been used for the containment of syphilis, tuberculosis, measles, smallpox, HIV/AIDS and Ebola ( Gyselen, 1994 ; Samoff et al, 2007 ; Lin et al, 2012 ; Greiner et al, 2015 ; Mbvinjo et al, 2021 ). It was adopted on a large scale around the world during the recent outbreak of COVID-19.…”
Section: Introductionmentioning
confidence: 99%